PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK MS GLOW CABANG PANBIL MALL KOTA BATAM - Dwi Astuti, Citra; Syaifullah (SCIENTIA JOURNAL, 2022)
Service quality is very important for every company, seen as a major factor in product selection. Customer fulfillment will be achieved if the quality of goods is in accordance with customer requirements. By providing good service to customers will greatly influence purchasing decisions and provide good final results for the company. Not only service quality but promotion is important in fostering a sense of belonging to the product. Promotion also provides good quality service to customers. Because by building good and clear services, it will have a positive impact on both parties to build mutual trust, with mutual trust and no hesitation. Many choices must be made by companies in creating promotional techniques at the individual item level. This analysis utilizes a descriptive study design through a quantitative approach. Using the SPSS application issue 25 to assist in this research. The sample used was 257 resource persons with random determination. Information collection is carried out through the provision of questionnaires, service quality and promotions were fairly distributed, where the independent variables were no multicollinearity and heteroscedasticity were found. When service quality has a definite good consequence on the desire to buy, and the promotion variable has a good consequence on the desire to buy. Meanwhile, the f test simultaneously defines if the service quality and supply variables have a good impact on the desire to buy.